The cultural grounding of tax issues: insights from tax audits. - Smith, Kent W. (Law & Society Review, 1995)
The cultural grounding of tax issues in the U.S. are discussed. Income tax laws are the central motivation for many to learn and utilize the basics of accounting. The process of collecting records, organizing the data into tax and accounting categories, and abstracting the information that is involved in preparing tax returns successfully draws individuals deeper into the culture of accounting. The issues raised during tax audits provide an insight into the difficulties that taxpayers have in comprehending and following accounting concepts and procedures. A study of state audits generally confirms the hypotheses and illustrates the grounding of taxpaying in accounting, and it is concluded that, whereas tax laws may draw people into this culture, the information that taxpayers gather and process frequently has utility for the taxpayers themselves.